# Calculator search results

Formula
Solve the system of equations
Graph
$x + y = 3$
$x - y = 1$
$x$Intercept
$\left ( 3 , 0 \right )$
$y$Intercept
$\left ( 0 , 3 \right )$
$x$Intercept
$\left ( 1 , 0 \right )$
$y$Intercept
$\left ( 0 , - 1 \right )$
$\begin{cases} x+y = 3 \\x-y = 1 \end{cases}$
$x = 2 , y = 1$
Solve quadratic equations using the square root
$\begin{cases} x + y = 3 \\ x - y = 1 \end{cases}$
 Solve a solution to $x$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \\ x - y = 1 \end{cases}$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \\ \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ y } = \color{#FF6800}{ 1 } \end{cases}$
 Substitute the given $x$ value into the equation $x - y = 1$
$\left ( \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
$\left ( \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
 Solve a solution to $y$
$\color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
$\color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
 Substitute the given $y$ value into the equation $x = - y + 3$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
$x = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \color{#FF6800}{ + } \color{#FF6800}{ 3 }$
 Add $- 1$ and $3$
$x = \color{#FF6800}{ 2 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ 2 }$
 The possible solutions are as follows 
$\color{#FF6800}{ x } = \color{#FF6800}{ 2 } , \color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ 2 } , \color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
 Check if it is the solution to the system of equations 
$\begin{cases} \color{#FF6800}{ 2 } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 3 } \\ \color{#FF6800}{ 2 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } = \color{#FF6800}{ 1 } \end{cases}$
$\begin{cases} \color{#FF6800}{ 2 } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 3 } \\ \color{#FF6800}{ 2 } \color{#FF6800}{ - } \color{#FF6800}{ 1 } = \color{#FF6800}{ 1 } \end{cases}$
 Simplify the equality 
$\begin{cases} \color{#FF6800}{ 3 } = \color{#FF6800}{ 3 } \\ \color{#FF6800}{ 1 } = \color{#FF6800}{ 1 } \end{cases}$
$\begin{cases} \color{#FF6800}{ 3 } = \color{#FF6800}{ 3 } \\ \color{#FF6800}{ 1 } = \color{#FF6800}{ 1 } \end{cases}$
 Since it is true in both equations, it is the solution of the system of equations 
$\color{#FF6800}{ x } = \color{#FF6800}{ 2 } , \color{#FF6800}{ y } = \color{#FF6800}{ 1 }$
 그래프 보기 
Graph
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture